Perhitungan Harga Pokok Produksi Menggunakan Metode Job Order Costing Pada CV Jepara Meubel - Jarir Aziz Hizbulloh; Bima Aulia Cahaya Pranata Poeatra; Bagas Ridwan Suratama; Ribangun Bambang Jakaria (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The research was conducted to solve the problem of determining the price of goods of production correctly based on the cost of raw materials, labor costs, and overhead costs on the CV xxx of previously priced traditional managers which resulted in sales sometimes felt too expensive and sometimes earned too small profits. Quantitative descriptive research is used to solve this problem to produce conclusions from data related to the determination of substantive prices based on the method of Job Order Costing. The main object of the CV xxx is a detailed note of the need in the manufacture of glass wardrobes and classic dress wardros. The data used in this research are primary data and skunder data, i.e., primary Data is the details of raw materials, raw material specifications, price per unit of raw material, labour cost, etc. Whereas data skunder is a discipline related to the methods of research that can help solve the question of determination of the price of the substance. Research shows results where based on the traditional management of CV xxx, there is a mistake in determining overhead costs. This confusion is detrimental to the company in getting too low profits. Comparison of previous management with the Job Order Costing method can find out where a particular variable should be in the overhead cost category in order to obtain the price of the production commodity that can determine the company's losses.